The analysis of tourism development strategies using Tourism Area Life Cycle Theory in Sumberpakem Village, Sumbejambe District - Margaretta Andini Nugroho (Universitas Merdeka Malang, 2024)
The development of tourism in Sumber Pakem Village has experienced ups and downs. This tourism has been operating since 2019 with the concept of batik educational tourism, but tourist visits are few. In December 2021, the Village Government innovated by establishing a Batik Cultural House, inaugurated as an Eduwisata Village. This effort is only temporary, in 2023 the Batik Cultural House will no longer be operating. This condition threatens the sustainability of Sumber Pakem tourism. This study aims to formulate a strategy for developing Sumber Pakem tourism so that it can survive. Tourism Area Life Cycle (TALC) is the right concept to determine the life cycle of a tourist attraction. This concept can formulate a strategy to revive a tourist attraction, each stage in the TALC model has different characteristics, challenges, and obstacles. Therefore, a different development strategy is needed. This study aims to analyze the position of the life cycle of Sumber Pakem Village appropriately, so that an appropriate and sustainable tourist attraction development strategy can be formulated. The analysis method used is descriptive qualitative. collection of primary and secondary data through interviews and direct observation. The technique for determining informants is purposive sampling. The data analysis technique used triangulation which was then analyzed using TALC and SWOT theories. The results of the study showed that the development of Sumber Pakem Village was in the Involvement cycle, so the strategy that must be implemented is to increase the involvement of pentahelix elements in the tourism planning and development process.